Use of Herbal Medicine among Pregnant Women Referring to Valiasr Hospital in Kazeroon, Fars, South of Iran - M Tabatabaee (Institue of Medicinal Plants, ACECR, 2011)
Background: The increase in the use of herbal products is noticed all over the world. The safety of herbal drugs becomes particularly important in pregnant women and children. Despite the fact that available data are insufficient to justify herbal use during pregnancy, exposure to herbal products is frequent in these subjects. Some of the more complex reasons for preference of herbal medicine are associated with cultural and personal beliefs and philosophical views toward life and health. The present study was conducted to evaluate drug utilization pattern during pregnancy in Kazeroon, south of Iran. Methods: In all, 530 women fulfilling study inclusion criteria were interviewed at the postnatal ward of Valiasr hospital in Kazeroon, from September to October 2009. Results: In all, 158 out of the 513 women (30.8%) had used herbal drugs during pregnancy. The most commonly used herbs in pregnancy in this study were Ammi, Saatar and Sweet Basil. The most usuall period of using herbal drugs was throughout the first trimester of pregnancy. There was no statistical difference between women using and those not using herbal drugs in pregnancy. In most instances, the women reported to have been recommended herbal drug use by family (87.3%). Conclusion: In spite of the fact that side effects and teratogenic potentials of most herbal products are poorly understood, indiscriminate use of herbal remedies in different forms is very rampant. Pregnancy care providers should be aware of the common herbal supplements used by women, and of the evidence regarding potential benefits or harm.